2015
DOI: 10.1038/nrneph.2015.162
|View full text |Cite
|
Sign up to set email alerts
|

The glycocalyx—linking albuminuria with renal and cardiovascular disease

Abstract: Albuminuria is commonly used as a marker of kidney disease progression, but some evidence suggests that albuminuria also contributes to disease progression by inducing renal injury in specific disease conditions. Studies have confirmed that in patients with cardiovascular risk factors, such as diabetes and hypertension, endothelial damage drives progression of kidney disease and cardiovascular disease. A key mechanism that contributes to this process is the loss of the glycocalyx--a polysaccharide gel that lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 111 publications
5
128
1
1
Order By: Relevance
“…Although pleiotropic effects have been inferred, improved glycemic control, lowering of blood pressure, decrease in intraglomerular pressure, reduction in albuminuria, and amelioration of volume overload are all plausible protective mechanisms. 4,[13][14][15][16][17][18][19][20][21][22][23] The effects on cardiovascular and renal outcomes observed within this program of two integrated trials are similar to those observed previously with this drug class. 5,6 The favorable direction of effect with respect to stroke observed in this trial program differs from a previously reported possible adverse effect on stroke risk.…”
Section: Placebo Better Canagliflozin Bettersupporting
confidence: 63%
“…Although pleiotropic effects have been inferred, improved glycemic control, lowering of blood pressure, decrease in intraglomerular pressure, reduction in albuminuria, and amelioration of volume overload are all plausible protective mechanisms. 4,[13][14][15][16][17][18][19][20][21][22][23] The effects on cardiovascular and renal outcomes observed within this program of two integrated trials are similar to those observed previously with this drug class. 5,6 The favorable direction of effect with respect to stroke observed in this trial program differs from a previously reported possible adverse effect on stroke risk.…”
Section: Placebo Better Canagliflozin Bettersupporting
confidence: 63%
“…There is substantial evidence to suggest that structural defects in the GFB are largely a result of albuminuria in specific disease conditions [27], which could explain why we do not see any structural abnormalities in our model.…”
Section: Discussionmentioning
confidence: 87%
“…Only recently the role of glycocalyx and the adverse effects of its deterioration in several diseases has been accepted [55], for instance, its dysfunction contributes to renal and cardiovascular disease progression, associated with albuminuria [26] and its degradation is recognized in septis with the onset of acute lung injury in most severe cases [56]. In acute lung injury and acute respiratory distress syndrome, pulmonary edema was observed, correlated to glycocalyx deterioration [57].…”
Section: Discussionmentioning
confidence: 99%
“…Glycocalyx degeneration, induced by reactive oxygen species exposure, has been shown to lead to endothelial dysfunction, with possible onset of microalbuminuria or proteinuria (i.e. the presence of an excess of albumin or other serum proteins in the urine) in clinical diseases [24,25], and subsequently to vascular inflammation and cardiovascular disease progression [26].…”
Section: Introductionmentioning
confidence: 99%